Association of Cardiac MRI–derived Aortic Stiffness with Early Stages and Progression of Heart Failure with Preserved Ejection Fraction - Schulz, Alexander; Schellinger, Isabel N.; Backhaus, Sören J.; Adler, Ansgar S.; Lange, Torben; Evertz, Ruben; Kowallick, Johannes T.; Hoffmann, Annett; Matek, Christian; Tsao, Philip S.; Hasenfuß, Gerd; Raaz, Uwe; et al. (Radiology: Cardiothoracic Imaging, 2024)
Purpose: To investigate if aortic stiffening as detected with cardiac MRI is an early phenomenon in the development and progression of heart failure with preserved ejection fraction (HFpEF). Materials and Methods: Both clinical and preclinical studies were performed. The clinical study was a secondary analysis of the prospective HFpEF stress trial (August 2017 through September 2019) and included 48 participants (median age, 69 years [range, 65–73 years]; 33 female, 15 male) with noncardiac dyspnea (NCD, n = 21), overt HFpEF at rest (pulmonary capillary wedge pressure [PCWP] ≥ 15 mm Hg, n = 14), and masked HFpEF at rest diagnosed during exercise stress (PCWP ≥ 25 mm Hg, n = 13) according to right heart catheterization. Additionally, all participants underwent echocardiography and cardiac MRI at rest and during exercise stress. Aortic pulse wave velocity (PWV) was calculated. The mechanistic preclinical study characterized cardiac function and structure in transgenic mice with induced arterial stiffness (Runx2-smTg mice). Statistical analyses comprised nonparametric and parametric comparisons, Spearman correlations, and logistic regression models. Results: Participants with HFpEF showed increased PWV (NCD vs masked HFpEF: 7.0 m/sec [IQR: 5.0–9.5 m/sec] vs 10.0 m/sec [IQR: 8.0–13.4 m/sec], P = .005; NCD vs overt HFpEF: 7.0 m/sec [IQR: 5.0–9.5 m/sec] vs 11.0 m/sec [IQR: 7.5–12.0 m/sec], P = .01). Increased PWV correlated with higher PCWP (P = .006), left atrial and left ventricular long-axis strain (all P < .02), and N-terminal pro–brain natriuretic peptide levels (P < .001). Participants with overt HFpEF had higher levels of myocardial fibrosis, as demonstrated by increased native T1 times (1199 msec [IQR: 1169–1228 msec] vs 1234 msec [IQR: 1208–1255 msec], P = .009). Aortic stiffness was independently associated with HFpEF on multivariable analyses (odds ratio, 1.31; P = .049). Runx2-smTG mice exhibited an “HFpEF” phenotype compared with wild-type controls, with preserved left ventricular fractional shortening but an early and late diastolic mitral annulus velocity less than 1 (mean, 0.67 ± 0.39 [standard error of the mean] vs 1.45 ± 0.47; P = .004), increased myocardial collagen deposition (mean, 11% ± 1 vs 2% ± 1; P < .001), and increased brain natriuretic peptide levels (mean, 171 pg/mL ± 23 vs 101 pg/mL ± 10; P < .001). Conclusion: This study provides translational evidence that increased arterial stiffness might be associated with development and progression of HFpEF and may facilitate its early detection.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Animal Studies; Aorta; Cardiac; Heart; MR Functional Imaging; MR Imaging